Factors affecting acceptance of organ donation in mainland China: A national cross‐sectional study - Zhang, Xinyue; Zheng, Xutong; Chen, Tianle; Li, Yiqi; Wang, Yinlin; Chen, Jiaxi; Ye, Xinxin; Zhang, Xun; Wang, Yujia; Ming, Wai‐Kit; Sun, Xinying; Xiang, Ze; et al. (Journal of clinical nursing, 2023)
Aims and Objectives To explore the acceptances and associated influences of organ donation in mainland China. Background The shortage of organ donors has limited the development of organ transplantation in China. It is important to recognise the target population who has high intention to donate their organs may change the status. Design We conducted a cross‐sectional, multi‐stage sampling study collected demographic data and individuals' willingness to accept organ donation. Methods A stepwise linear regression analysis was adopted to evaluate the factors related to the attitudes toward organ donation. Results We collected 11,031 valid samples for the survey. The willingness to donate organs among Chinese residents averaged 56.93 points. To be specific, males (β = −.03), religious believers (β = −.01) and parents with a different number of children (all: β = −.04) are less willing to donate their organs. Respondents who live in an urban area (β = .03), have higher education level (High school or junior college β = .04, Bachelor degree or above β = .09), feel anxious (mild, moderate β = .02), feel pressured (moderate, severe β = .08), have higher scores of the Short‐Form Health Literacy Instrument (HLS‐SF12) (β = .31), The Self‐Management Scale (SHMS) (β = .16), EuroQol Five Dimensions Questionnaire (EQ‐5D) (β = .04) and EuroQol Visual Analogue Scale (EQ‐VAS) (β = .24), are more positive to donate. Conclusions This study firstly discusses the public acceptance of organ donation through a nationwide sample around China. In this study, we discovered that Chinese residents' acceptance level of organ donation and that gender, house, anxiety, pressure, social support and health literacy were the main influencing factors on residents' attitudes. Relevance to Clinical Practice To figure out the Chinese public acceptance and its influencing factors of organ donation can help nurse transplant coordinators to recognise the target population and the obstacles of organ donation. Patient or Public Contribution At the phase of collecting data, participants were recruited to fill the questionnaires.